Where Am I? A new case of developmental topographical disorientation - Bianchini, Filippo; Palermo, Liana; Piccardi, Laura; Incoccia, Chiara; Nemmi, Federico; Sabatini, Umberto; Guariglia, Cecilia (Journal of neuropsychology, 2014)
Recently, developmental topographical disorientation (DTD) was described (Bianchini et al., 2010, J Clin Exp Neuropsychol, 20, 807–27; Iaria & Barton, 2010, Exp Brain Res, 206, 189–96; Iaria, Bogod, Fox, & Barton, 2009, Neuropsychologia, 47, 30–40) as a navigational deficit in the absence of neurological or psychiatric disorders. Here, we reported the case of a healthy subject who presented this disorder. Dr. WAI was a 29‐year‐old right‐handed man with normal development and no clinical history of neurological or psychiatric diseases who was affected by a very pervasive topographical orientation and navigational disorder. A neuroradiological exam confirmed the absence of structural and anatomical alterations of the brain. Dr. WAI was submitted to an extensive neuropsychological examination and to a battery of tests specifically developed to assess developmental topographical disorder. Using this battery, we analysed Dr. WAI's acquisition of navigational information and re‐orientation processes. He showed severe DTD accompanied by deficits of different cognitive processes directly or indirectly involved in navigational skills. Dr. WAI showed a deficit in developing cognitive maps, already found in previous cases, plus difficulties in evaluating distances and computing metric environmental features. He represents a further confirmation of the existence of DTD suggesting dissociations within the disorder related to the level of development of the ability to build cognitive maps and the association of different imagery deficits. Dr. WAI can help in shedding some light on the mechanisms underlying lack of development of navigational skills.